Kajian Strategi Keberlanjutan UMKM Berbasis Rumah/HBE Pengolahan Bandeng di Kampung Tematik Bandeng Krobokan Semarang - Siti Nur Habibah; Wido Prananing Tyas (Jurusan Perencanaan Wilayah dan Kota, 2021)
Home-based enterprise (HBE) is a micro, small to medium scale enterprise located at home. HBE is easily built but also very vulnerable. Milkfish processing HBE in Krobokan can sustain for years. This study aims to determine the sustainability strategy of milkfish processing HBE in Krobokan Thematics Kampong based on sustainable livelihood approach theory. The method used is case study with qualitative descriptive analysis to analyze data from interview, observation, questionnaire and literature study data. A total of 11 HBE's are studied in regard to their livelihood capital, level of sustainability and strategies that they used. The study found that HBE operators are using strategy related to livelihood capitals which are human capital, natural capital, physical capital, social capital and financial capital. HBE sustainability strategies are intensification, extensification and diversification.